Socioeconomic gradients in child development in very young children: Evidence from India, Indonesia, Peru, and Senegal - Fernald, Lia C. H.; Kariger, Patricia K.; Hidrobo, Melissa; Gertler, Paul J. (Proceedings of the National Academy of Sciences, 2012)
Gradients across socio-economic position exist for many measures of children's health and development in higher-income countries. These associations may not be consistent, however, among the millions of children living in lower- and middle-income countries. Our objective was to examine child development and growth in young children across socio-economic position in four developing countries. We used cross-sectional surveys, child development assessments, measures of length (LAZ), and home stimulation (Family Care Index) of children in India, Indonesia, Peru, and Senegal. The Extended Ages and Stages Questionnaire (EASQ) was administered to parents of all children ages 3–23 mo in the household ( n =8,727), and length measurements were taken for all children 0–23 mo ( n = 11,102). Household wealth and maternal education contributed significantly and independently to the variance in EASQ and LAZ scores in all countries, while controlling for child's age and sex, mother's age and marital status, and household size. Being in the fifth wealth quintile in comparison with the first quintile was associated with significantly higher EASQ scores (0.27 to 0.48 of a standardized score) and higher LAZ scores (0.37 to 0.65 of a standardized score) in each country, while controlling for maternal education and covariates. Wealth and education gradients increased over the first two years in most countries for both EASQ and LAZ scores, with larger gradients seen in 16–23-mo-olds than in 0–7mo-olds. Mediation analyses revealed that parental home stimulation activities and LAZ were significant mediating variables and explained up to 50% of the wealth effects on the EASQ.